Self-efficacy among kindergarten department students in the faculties of basic education in universities of KRG / Iraq according to some variables - Othman , Dlvin Omar; Ali , Seenaa Ahmad (Zanco Journal of Human Sciences, 2023)
The current research aims to identify: level of self-efficacy among kindergarten department students in the Faculties of Education in the universities of the Kurdistan Region/Iraq, and the significance of difference in level of self -efficacy among students according to the variables (university , academic stage, social status and economic status), and the researchers used the descriptive approach to implement the research procedures, the research community is students of the kindergarten department in the faculties of the basic education in the universities of the Kurdistan region, which contains (1207) students for the academic year 2021-2022, Research sample was chosen by stratified random method forming (490) students distributed in universities of KRG in the following form: Salahaddin University (274), Sulaymaniyah University (284), Halabja University (168), University of Garmiyan (232), Raparin University (285), and goals of the research has been achieved by building the scale of self -efficacy, and it is consisted of (40) paragraphs with alternative answers (always, often, sometimes, rarely, never), and giving grades (5, 4, 3, 2 and 1) to alternatives, and the validity of the scale was extracted, as well as the researchers extracted the Psychometric characteristics of the Self efficiency scale, and the stability of the scale reached (0.81) using Cronbach’s alpha, and the researchers used the statistical bag represented by (Person's coefficient, t-test, Cronbach’s alpha), and the research reached the following results: that students of the kindergarten department in the basic education colleges in universities of KRG has a high level of self -efficacy, there are differences in the level of self -efficacy between Salahaddin University and Raparin University and for the benefit of Salahaddin University, and between Halabja University and Raparin University for the benefit of Halabja University, in the light of research results researchers recommended: A suitable mechanism to work on developing self -efficiency for students because of its great importance in their working lives, and they suggested: self-efficacy and its relationship to other variables such as (psychological adaptation, academic achievement).